Assessment of The Learning Outcomes of Physical Education in Children with Intellectual Disabilities - Andry Akhiruyanto; Taufiq Hidayah; Dewangga Yudhistira; Harinda Fahmi (Yayasan Keluarga Guru Mandiri, 2022)
Adaptive physical education is a type of physical education geared toward children with special needs, such as intellectual disabilities. Of course, there must be an assessment in learning to see if the results taught from the cognitive, affective, and psychomotor perspectives were achieved. The goal of this research was to learn more about how physical education learning outcomes were assessed in schools for students with intellectual disabilities in Semarang. The research method used was descriptive. This method aims to describe the events and circumstances that occurred. The research approach used was qualitative. Data were gathered through observation, interviews, and documentation. The informant for this study was a Semarang-based special school teacher (SLB) who teaches physical education classes. The findings revealed that teachers had difficulty making assessments for mentally retarded students even though the assessment was still conducted as it should. It was determined that the teacher conducted a cognitive, affective, and psychomotor assessment of physical education learning and modified the assessment indicators to find appropriate standards. Meanwhile, the assessment was carried out based on the students' abilities.